6‐mm‐long implants loaded with fiber‐reinforced composite resin‐bonded fixed prostheses (FRCRBFDPs). A 5‐year prospective study. Issue 12 (28th March 2017) - Rossi, Fabio; Lang, Niklaus P.; Ricci, Emanuele; Ferraioli, Lorenzo; Marchetti, Claudio; Botticelli, Daniele
Abstract: Aim: To evaluate the clinical and radiographic outcomes and the survival rates of fiber‐reinforced composite resin‐bonded fixed prostheses (FRCRBFDPs) placed in the posterior area supported by two short (6 mm) implants. Materials and Methods: Twenty consecutive patients received 40 SLActive 6‐mm‐long implants with a diameter of 4.1 mm ( n  = 29) or 4.8 mm ( n  = 11). Insertion torques and RFA (Resonance Frequency Analysis) were measured at implant installation. The prosthetic rehabilitation was performed after 8 weeks from insertion with a screw‐retained two‐ or three‐unit fixed dental prosthesis fabricated of FRCRBFDPs. Implant survival rates and marginal bone levels were evaluated at various time intervals until 5 years after loading. Results: Two of 20 patients lost four implants supporting two FRCRBFDPs between the second and the third year of follow‐up (cumulative survival rate: 90% after 5 years). Four patients suffered a fracture of the prosthetic reconstruction, and the success rate of the rehabilitation was 70% after 5 years. A mean marginal bone loss of 0.30 ± 0.34 mm was found after 5 years of function at the remaining implants. Conclusion: The survival of short implants was 90% owing to two bridges losses in the maxilla. However, the success rate of FRCRBFDPs over 5 years was only at 70%.